Espacios y diálogos renovados en la relación chileno-peruana - Milet, Paz (2022)
© de los textos: André Robelledo (Chile), Cristian Ovando Santana (Perú), Fabián Novak (Perú), Jaime Abedrapo (Chile), Luis García-Corrochano (Perú), Paula Solar (Chile), Paz Milet (Chile), Pedro Gamio (Perú), Ramiro Escobar (Perú), Ricardo Jiménez Palacios (Perú)